Towards an optimal aiming for molten salt power towers. (October 2017) - Flesch, Robert; Frantz, Cathy; Maldonado Quinto, Daniel; Schwarzbözl, Peter
Highlights: Application of aim point optimization for molten salt receivers. Detailed description of fast thermal model for calculation of molten salt receivers. Optimized aim point strategy outperforms parameter based aiming by more than 2%. Abstract: Finding a suitable aiming strategy for receivers of power towers can be challenging, especially for receivers using molten salt as heat transfer fluid as the allowable flux density decreases dramatically with increasing salt temperature. In this paper a very fast, steady-state model for the molten salt receiver is presented. This model is combined with a ray-tracing software and a metaheuristic optimization procedure. The thermal model is used to calculate the actual temperature and mass flow in the receiver which are then used to calculate the operational limits for the flux density. It is demonstrated that such an optimized aiming strategy can outperform a parameter based aiming strategies by more than 2%.